2018
DOI: 10.1186/s12916-018-1004-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the impact of the pneumococcal conjugate vaccine programme on pneumonia, sepsis and otitis media hospital admissions in England using a composite control

Abstract: BackgroundThe seven-valent pneumococcal conjugate vaccine (PCV) was introduced in England in September 2006, changing to the 13-valent vaccine in April 2010. PCV impact on invasive pneumococcal disease (IPD) has been extensively reported, but less described is its impact on the burden of pneumonia, sepsis and otitis media in the hospital.MethodsUsing details on all admissions to hospitals in England, we compared the incidence of pneumococcal-specific and syndromic disease endpoints in a 24-month pre-PCV period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 32 publications
5
78
1
Order By: Relevance
“…Reductions in AC‐CAP hospitalizations of 36%, 20% and 16% in children <2, 2–4 and 5–17 years of age, respectively, and even more pronounced decreases in PL‐CAP, are consistent with reports from most other countries . These findings are concordant with previous publications from Sweden that reported up to 37% reduction of inpatient all‐cause pneumonia in children < 2 years in 2012 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Reductions in AC‐CAP hospitalizations of 36%, 20% and 16% in children <2, 2–4 and 5–17 years of age, respectively, and even more pronounced decreases in PL‐CAP, are consistent with reports from most other countries . These findings are concordant with previous publications from Sweden that reported up to 37% reduction of inpatient all‐cause pneumonia in children < 2 years in 2012 .…”
Section: Discussionsupporting
confidence: 92%
“…However, in a recent study that adjusted for secular trends using the synthetic control method, there was no observed reduction of hospitalization for all‐cause pneumonia after PCV‐CIP introduction in any of five countries in the Americas (the United States, Mexico, Ecuador, Brazil and Chile) . Neither was there a reduction in pneumonia among the elderly in Australia, and studies from the UK and Denmark have observed similar increases of AC‐CAP in the elderly as in our study . Our results are in accordance with the moderate impact of the PCV‐CIP on the IPD incidence in the elderly observed both in Sweden, and in a multinational European study .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations